Beyond Amateurism: The Rebranding of Major College Athletics - Dallas Branch; Olin Adams; Marie Kraska (Journal of Applied Marketing Theory, 2015)
For decades prior to NCAA v. Board of Regents, the brand of college athletics, even at the highest level, was amateurism. However, the last three decades of surging revenues and costs, as well as the current wave of litigation challenging amateurism, force decision makers in major college athletics to contemplate a future in which amateurism is banished or in retreat. In sum, the brand has outgrown amateurism. Major college athletics can survive a paradigm shift by selling the action in its games, the game day experience, and the traditions of the institutions.